Foreign investment in the petroleum and mineral industries : (Published for Resources for the Future by Johns Hopkins Press, 1971)
Raymond F. Mikesell deals with sources of conflict between private foreign investors and the governments of developing countries. He concludes that government ownership and control will expand and that foreign investors are most likely to become sellers of their special services rather than remain investors who act freely for the benefit of parent companies. Originally published in 1971.